2021
DOI: 10.1177/0033354920988610
|View full text |Cite
|
Sign up to set email alerts
|

Establishing an Epidemiologic Profile of Hepatitis C Virus Infection at the Los Angeles County Jail

Abstract: Objective The hepatitis C virus (HCV) is the most common blood-borne infection in the United States. Although 2% to 3% of the global population is estimated to be infected with HCV, an estimated 18% of the US prison population may be infected. The objective of this study was to establish an epidemiologic profile of HCV infection in the largest urban jail system in the United States. Methods We retrospectively analyzed 20 years of data on demographic characteristics, risk factors, and HCV positivity among 80 68… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Adverse impacts of homelessness have been documented in Southern California communities (Abramson, Sanko, and Eckstein, 2021;Qureshi et al, 2021;Salem et al, 2020). For example, a study in 2020 found significantly elevated rates of posttraumatic stress symptoms among formerly incarcerated homeless women in Los Angeles County (Salem et al, 2020).…”
Section: Role Of Housing As a Social Determinant Of Healthmentioning
confidence: 99%
“…Adverse impacts of homelessness have been documented in Southern California communities (Abramson, Sanko, and Eckstein, 2021;Qureshi et al, 2021;Salem et al, 2020). For example, a study in 2020 found significantly elevated rates of posttraumatic stress symptoms among formerly incarcerated homeless women in Los Angeles County (Salem et al, 2020).…”
Section: Role Of Housing As a Social Determinant Of Healthmentioning
confidence: 99%
“…Test results for HCV infection were positive in 34.6% but they also included HCV antibody test, and not only detectable HCV RNA or HCV genotype. 10 These rates, however, all exceed the 1% prevalence in the general population 11 and this is due to the higher prevalence of risky behaviors among prisoners. 12 In the past, only a minority of prisoners infected by HCV were tested and treated, mainly because of inaccessible resources, untrained staff, short incarceration time, and the potential interruption of treatment when transferred to the community.…”
Section: Introductionmentioning
confidence: 97%
“…Test results for HCV infection were positive in 34.6% but they also included HCV antibody test, and not only detectable HCV RNA or HCV genotype. 10 These rates, however, all exceed the 1% prevalence in the general population 11 and this is due to the higher prevalence of risky behaviors among prisoners. 12 …”
Section: Introductionmentioning
confidence: 98%